Long Term Cosmetic Application Improves Tactile Discrimination in the Elderly; a New Psychophysical Approach - Aimonetti, Jean-Marc; Deshayes, Claire; Crest, Marcel; Cornuault, Pierre-Henri; Weiland, Benjamin; Ribot-Ciscar, Edith (Frontiers in Aging Neuroscience, 2019)
Introduction: Tactile sensitivity is impaired in older adults, which contributes to the loss of manual dexterity and mobility function. The reliability of classical psychophysical tests, such as two-point gap discrimination, has been questioned. Here we tested a new method to determine tactile acuity during dynamic touch, which is more functional than static touch. The aim was to validate a method providing a high level of discrimination of tactile acuity in the elderly. Methods: We tested the ability of subjects to evaluating the distance between bands printed on poly-methyl-methacrylate sheets. Pairs of sheets were compared in two groups of participants aged from 60 to 74 years; the test group was required to apply a cosmetic foam with an active ingredient on both their hands twice a day for one month, the control group had an identical task, but used the same cosmetic foam without any active ingredient. The tests were run in a double-blind, placebo-controlled study. Results: The tactile discrimination threshold decreased by 83 µm after one month of cosmetic application in the group using the active ingredient while it was unchanged in the control group. Discussion: The test presented here provided highly accurate results and should be useful to determine tactile performance. It allows the monitoring of tactile rehabilitation and/or skin treatments used to restore tactile acuity in the elderly.